2012
DOI: 10.1097/bpo.0b013e31824b6e00
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential Fusion With Anterior Strut Grafting and Short-segment Multipoint Posterior Fixation for Burst Fractures in Skeletally Immature Patients

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Ilharreborde also pointed out the reduction in operative time and blood loss in comparison to a group of patients treated with thoracic hook hybrid constructs [10]. In addition, the polyester bands indications have recently been extended to traumatology, with promising results [25,26]. However, approaching the canal carries a potential risk of neurological injury.…”
Section: Discussionmentioning
confidence: 95%
“…Ilharreborde also pointed out the reduction in operative time and blood loss in comparison to a group of patients treated with thoracic hook hybrid constructs [10]. In addition, the polyester bands indications have recently been extended to traumatology, with promising results [25,26]. However, approaching the canal carries a potential risk of neurological injury.…”
Section: Discussionmentioning
confidence: 95%
“…Anterior or far lateral corpectomy and strut grafting, followed by either anterior or posterior instrumentation with arthrodesis, is an alternative strategy of fixation. 28,30 …”
Section: Burst Fracturesmentioning
confidence: 99%
“…They concluded that regardless of the severity of injury, no technique was able to correct and maintain the fracture segment to the physiological level and kyphotic angle. This statement was reaffirmed by Wang et al, who also found no correlation between the degree of kyphosis and residual back pain [14]. More studies are needed to understand the effect of short fixation on adjacent levels and on the maintenance of deformity correction in the thoracolumbar spine, either as a stand-alone procedure or as an adjunct to anterior fixation.…”
Section: Angle Of Correctionmentioning
confidence: 92%